(untitled) (Anclajes, 2024)
This interview was motivated by the lecture given by professor and researcher Marcy Schwartz in March 2023 at the Faculty of Philosophy and Humanities of the National University of Córdoba (UNC), Argentina, as well as the publication of her first book to be translated to Spanish. The conversation highlights Schwartz’s stimulating work about the complex and always heterogeneous links between Latin American urban cultures, archives, remains, the archivable and the unarchivable as a possibility of knowledge.